Record-high Glass coefficient in the shift current response of a ferroelectric halide perovskite - Koma Miki; Masao Nakamura; Asahi Yamada; Gurvan Bosser; Kiyohiro Adachi; Daisuke Hashizume; Naoki Ogawa; Satoshi Okamoto; Yoshinori Tokura; Masashi Kawasaki (Proceedings of the National Academy of Sciences, 2026)
Ferroelectric halide perovskites provide a fertile platform for optoelectronic functions based on the bulk photovoltaic effect, where broken inversion symmetry couples with quantum geometry of wave functions. The most prominent manifestation is the shift current, second-order nonlinear photocurrent arising from change in the Berry connection during optical transitions. Here we report a gigantic shift current response in epitaxial thin films of a lead-free ferroelectric halide perovskite CsGeI 3 . High-quality films grown by molecular beam epitaxy exhibit clear hallmarks of shift current, including spectral sign reversals, light-polarization dependence, and reversible electric-field modulation associated with switchable ferroelectric polarization. Remarkably, the normalized shift current magnitude surpasses those ever reported for other compounds by more than an order of magnitude, establishing a benchmark for bulk photovoltaic performance. These results identify ferroelectric halide perovskites as a powerful platform for exploring quantum-geometry-driven photoresponses and open a pathway toward next-generation photovoltaic and nonlinear optoelectronic technologies beyond the conventional junction-based architectures.